Ex-ante and ex-post regulation: Does the joint use improve on social welfare? - Sverre Ole Grepperud (University of Oslo, 2023)
A principle-agent model is applied to discuss the relationship between ex-ante regulation (standards) and ex-post regulation (firm and worker fines). Accident risks (e.g. medical errors) are affected by decisions made both by the firm (hospital) itself and the employees of the firm (healthcare workers), the regulator observes the safety efforts of the firm and (a share of) the occurrences of accidents, while worker safety efforts are non-contractible. We find that standards and firm fines are substitutes since their joint use does not improve social welfare relatively to their exclusive use. However, standards and worker fines become complements (the joint use improves social welfare relative to their exclusive use) in the presence of firm-related accident costs.